White blood cell count rating and neutrophil percentage during labor and in early postpartum period - Lebdowicz, Joanna; Torbé, Dorota; Bulsa, Marek; Torbé, Andrzej (Journal of Education, Health and Sport, 2018)
Objectives: To characterize postpartum WBC count and neutrophil percentage in relation to mode of delivery in various clinical situations.Material and methods: 317 participants near term of labor were included to the study and then divided into four groups:1. Group PROM (n=97) - women with labor onset after membranes rupture and spontaneous vaginal delivery (PROM – premature rupture of membranes)2. Group non-PROM (n=133) - women with labor onset at intact membranes and spontaneous vaginal delivery3. Group ELCS (n=58) - women who delivered by cesarean section for elective indications (ELCS – elective cesarean section)4. Group EMCS (n=29) - women who delivered by cesarean section for emergency indications.Venous blood sampling for WBC count and neutrophils percentage calculation was done in the course of labor or strictly before elective caesarean section and, subsequently, on the second day of puerperium.Results: A statistically significant difference in the WBC count during labor in women with PROM relative to non-PROM and EMCS groups was found. In non-PROM group WBC count was higher than in ELCS patients. In EMCS patients leukocyte count was higher than in ELCS group. The percentage of neutrophils during labor in EMCS group was higher than in the PROM and ELCS groups. On the second postpartum day WBC count of PROM, ELCS and EMCS patients was significantly higher than in the non-PROM group. Higher leukocyte count at the second day of puerperium was also found in the group of EMCS, relative to ELCS. The percentage of neutrophils in the blood at the second day after delivery in ELCS and EMCS groups was higher than in the patients with intact, as well as with ruptured membranes. WBC count on the second day post delivery was higher than its values in labor in ELCS, EMCS and PROM groups. The percentage of neutrophils in labor in PROM and non-PROM groups significantly exceeded its values on the second postpartum day.Conclusions: 1. WBC count values in early puerperium in women after cesarean section are higher than in women whose labor was started at intact fetal membranes and was finished in natural way.2. WBC count values in early puerperium are higher after emergency cesarean section than after elective cesarean delivery. 3. The percentage of neutrophils in the early puerperium in patients after cesarean section is higher than in those after natural delivery.4. A significant increase in the value of WBC count on the second day after delivery, in relation to its intrapartum values, occurs in women whose fetal membranes rupture occurs before the beginning of labor, as well as in women after cesarean section.5. After natural delivery, regardless of the state of the fetal membranes, there is an increase in the percentage of neutrophils which is not observed after cesarean section.6. Assessment of WBC count, as well as neutrophil percentage in the early puerperium are not useful as a sole markers for the presence of infectious morbidity and for making decisions about the implementation of antibiotic therapy.